Pooled analysis of two studies evaluating efficacy and safety of olopatadine hydrochloride 0.77% in patients with allergic conjunctivitis - McLaurin E (Dove Medical Press, 2017)
Eugene McLaurin,1 Mark Bergmann,2 Abhijit Narvekar,3 Adeniyi Adewale,3 Paul Gomes,4 Gail Torkildsen5 1Department of Ophthalmology, Total Eye Care, PA, Memphis, TN, 2Department of Ophthalmology, Apex Eye, Cincinnati, OH, 3Department of Ophthalmology, Alcon Research Ltd, Fort Worth, TX, 4Department of Ophthalmology, Ora Inc., 5Department of Ophthalmology, Andover Eye Associates, Andover, MA, USA Purpose: Two individual phase 3 conjunctival allergen challenge (CAC) studies of similar design have assessed the efficacy and safety of olopatadine hydrochloride (HCl) 0.77% for the treatment of allergic conjunctivitis. The purpose of this study is to evaluate the integrated efficacy and safety of olopatadine HCl 0.77% from a larger dataset by pooling data from the two individual CAC studies.Methods: Data were pooled from two phase 3, randomized, multicenter, double-masked, active- and vehicle-controlled CAC studies. The primary comparison was on ocular itching scores between olopatadine HCl 0.77% versus vehicle (at onset and 24 hours) and olopatadine HCl 0.77% versus olopatadine 0.2% (at 24 hours). Additional end points included conjunctival redness, total redness, and proportion of itching responders at onset and 24-hour duration of CAC. For both primary and secondary analysis, mixed model repeated measures analysis was used, except for proportion of ocular itching responders. Sensitivity analyses were carried out using a two-sample t-test.Results: This analysis included 448 patients. Olopatadine HCl 0.77% was superior to vehicle (P<0.0001) at onset and 24-hour duration of action (difference in means: -1.14 to -1.52) and to olopatadine 0.2% (P=0.0009) at 24-hour duration of action in relieving ocular itch. Additionally, olopatadine HCl 0.77% substantially reduced conjunctival redness and total redness over vehicle and olopatadine 0.2% at onset and 24-hour duration of action. At 24 hours CAC, there were a higher proportion of itching responders with olopatadine HCl 0.77% compared to vehicle or olopatadine 0.2% (difference in proportion of responders: 43.17%, P<0.0001, and 17.25%, P=0.0012, respectively). No safety concerns were identified.Conclusion: This analysis confirms the findings from the individual studies. The rapid onset and prolonged duration of action (for 24 hours) of olopatadine HCl 0.77% supports once-daily dosing in the treatment of allergic conjunctivitis. Keywords: olopatadine, allergic conjunctivitis, conjunctival allergen challenge, ocular itching, conjunctival redness